Children Unwelcome - Socio-physical Study of Children’s Community Toilets Usage in Mumbai’s Slums - Akov, Tamar; Satwah, Sunanda (European Journal of Sustainable Development, 2019)
In light of growing concerns among experts to achieve SDG 6.2 by 2030, and in view of the Swachh Bharat Mission – an initiative launched in 2014 to eradicate open defecation (OD) in India, this field research-based paper sets out to explore the physical and social enabling environment for children of informal settlements in Mumbai to use communal toilets. First stage of the research involved shortlisting 6 community toilets across 3 informal settlements and documenting them for spatial conditions and user experience. 2nd stage consisted of data collection from 986 random samples across all ages and genders, regarding usage patterns. The findings revealed that only 6.7% of the users were children. This led to the 3rd stage, where 80 children ages 14 and younger were interviewed, to understand their concerns, perceptions, habits and related interactions with adults. The research, spanning 18 months, exposed deficiency in the enabling environment to promote and sustain usage of toilets and diminish OD. Especially for children, the research revealed aspects of discrimination in the form of inequity bylaws; inappropriate ergonomics; adult intimidation; and parental indifference to sanitary choices. The paper suggests systemic children-specific mitigations, thereby lending a voice to their unique concerns and needs. Keywords: Children’s Sanitation, Enabling Environment, Discrimination & Exclusion, SDG 6.2, informal settlements